A Comparative Study of Immunological and Molecular Techniques to Diagnose Human Cytomegalovirus in renal Failure Patients in Diyala Governor - Ibtihal Hameed Mohsin; IbtesamBadday Hassan; Mohammed Abdul Daim Saleh (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Cytomegalovirus (CMV)belongsto the herpes virus family, it has the ability to cause systemic infection and serious diseases in immunocompromised patients such as hemodialysis patients. The aim of this study was to investigate the prevalence of CMV infectionamonghemodialysis (HD) patients.. Renal failure is a condition in which the kidneys fail to remove metabolic end-products from the blood and regulate fluid, electrolytes and pH balance of extracellular fluids.Renal failure diesease is a wide dissemination among kidney patients inBa’quba City.Aim: the study was carried out toImmunological andMolecular detection of CMV among renal failure patients whom admitted to IbnSina Center for kidney Dialysis in Baquba Teaching Hospital .Patients and Methods: This study was conducted for the period from 1/12/2019 to 15/6/2020 in Baquba city in Iraq ,The study involved a total of 100 patients (62 males and 38 females) with kidney diseasewith ageand 50 healthy individuals considered as controls.First step includes Human Cytomegalovirus (HCMV) diagnosis in studied groupsbyEnzyme-Linked Immunosorbent Assay technique(ELISA) and second step was detection of Human Cytomegalovirus(HCMV) by Real-time Polymerase Chain Reaction.Results: The obtained results showed that HCMV antibody was detected in renal failure patients by ELISAIgG (100%) while IgM were (15.0%) . Also,Distribution Of Detection of human cytomegalovirus DNA in serum between patients with renal failure and control by using sensitive molecular techniques, The obtainedresults showed that the HCMV DNA was detected in (6 out of 45) or 6 % in patients, while in control group (0 out of 5) or 0.0 %.Also, the HCMV DNA was detected in males 1(16.66) %. while in females was 5(83.34) %, while in control group (0 out of 5) or 0.0 %. with highly precent differences was noticing among both sexes. These results showed the age group 60-70 showed the highest rate of infection among other groups.Conclusions: Real time PCR was rapid, sensitive and useful for diagnosing CMV infection in such patients.The results showed that Cytomegalovirus has relationship with chronic and acute renal failure and can affect the patient’s immune status. our results can provide an advanced diagnosis of viral infections among patients in hospitals in Iraq.